Respuesta :

Answer:

3 + 9x = 11x - 7

simplify

9x + 3 = 11x - 7

subtract 11x from both sides

-11x             -11x

-2x + 3 = -7

get rid of constants first by subtracting by 3 from both sides

-3            -3

-2x = -10

divide both sides by -2 since that is the inverse operation of multiplication

/-2    /-2

X = 5

Answer:

x=5

Step-by-step explanation:

Hi, first the thing to do here is simple,

step 1, collecting like terms

3+9x=11x-7

11x-9x=3+7

2x=10

then divide both by 2.

x= 5

ACCESS MORE